George Bondor, Dansul măștilor. Nietzsche și filosofia interpretării (The Dance of Masks. Nietzsche and the Philosophy of Interpretation), ed. a 2-a, reviz. (second edition, revised), Editura Spandugion, București, 2020 - Vasile Cătălin BOBB (Studia Universitatis Babeș-Bolyai. Philosophia)
In the very first page of “Note on first edition” there is a remark not to be missed by a quick reading. The Dance of Masks. Nietzsche and the Philosophy of Interpretation is an extract or, in Bondor’s words, “the processing of the doctoral dissertation” called From Metaphisics to Hermeneutics. Fredrich Nietzsche. In other words, the philosophy of interpretation or the dance of masks is not only the “path” from metaphysics to hermeneutics but, to a certain extent, “the final point”. Of course, the leading figure that takes us on this journey with, I might add, in my eyes not in Bondor’s, no final destination is Fredrich Nietzsche. But, setting apart my one idiosyncrasies, we must see how George Bondor constructs the road, mediated by Nietzsche, from metaphysics to hermeneutics or, better yet, from metaphysics to interpretation (and, perhaps, we might also see what all these has to do with the “dance of masks”).